Mahātam Ekādašī : ḥāwī-i iršādāt ānči Šrī Krišan jīv az Arǧun farmūda - Devīprasāda (Nawal Kišūr, 1897)
On the significance of fasting on the eleventh day (Ekādaśī) of the lunar fortnights in Hindu calandar and associated rituals based on Puranas